Rural small-scale women farmers and preference for family size in South-East Nigeria - Samuel Okafor; Janefrances C. Onu; Vivian C. Nwaeze (Comparative Population Studies (CPoS), 2021)
Among other things, fertility control in Nigeria may not be feasible without recourse to socioeconomic issues such as micro-occupation classification and dominant family cultural traditions facing women and their relationship to fertility behaviour. Rural small-scale women farmers are a relatively closed group with some uniqueness for the understanding of the value of children (VOC) in socioeconomic and cultural contexts and its relationship with fertility behaviour in developing nations. This study, guided by the VOC model, focuses on determining factors for preference for family size (0-4 children) among rural small-scale women farmers in Eha-Amufun in Enugu state. 200 married women (mean age=33.9; mean age at marriage=24.5) from 20 agricultural co-operative societies were selected for the study. The study adopted a survey and quantitative research design. Besides the sociodemographic information of the study participants, the study elicited from the respondents information on their choice of family size, the connection of family size with their occupation and the circumstances surrounding son preference and son adoption in the family and rural contexts. The collected data were analysed using the ordinal logistic regression model. The findings show that economic independence, son preference and male child adoption negates limiting family sizes to 0-4 (p<.05) however, age, formal education, children as source of labour and economic independence were positively correlated with the desire for a family size of 4 children and above. In view of the limitations of the study and the ability of the VOC model to unveil spurious factors for fertility behaviour among women, there is a need for comparative studies of rural closed groups in developing nations and their fertility behaviour.Among other things, fertility control in Nigeria may not be feasible without recourse to socioeconomic issues such as micro-occupation classification and dominant family cultural traditions facing women and their relationship to fertility behaviour. Rural small-scale women farmers are a relatively closed group with some uniqueness for the understanding of the value of children (VOC) in socioeconomic and cultural contexts and its relationship with fertility behaviour in developing nations. This study, guided by the VOC model, focuses on determining factors for preference for family size (0-4 children) among rural small-scale women farmers in Eha-Amufun in Enugu state. 200 married women (mean age=33.9; mean age at marriage=24.5) from 20 agricultural co-operative societies were selected for the study. The study adopted a survey and quantitative research design. Besides the sociodemographic information of the study participants, the study elicited from the respondents information on their choice of family size, the connection of family size with their occupation and the circumstances surrounding son preference and son adoption in the family and rural contexts. The collected data were analysed using the ordinal logistic regression model. The findings show that economic independence, son preference and male child adoption negates limiting family sizes to 0-4 (p<.05) however, age, formal education, children as source of labour and economic independence were positively correlated with the desire for a family size of 4 children and above. In view of the limitations of the study and the ability of the VOC model to unveil spurious factors for fertility behaviour among women, there is a need for comparative studies of rural closed groups in developing nations and their fertility behaviour.
urn:nbn:de:bib-cpos-2021-02en3
Keywords: 300; Closed group; Desired family size; Fertility control; Rural small-scale farmers; VOC; Women's roles